2005
DOI: 10.1159/000088860
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Disorder, Factor-Analyzed Symptom Dimensions and Serotonin Transporter Polymorphism

Abstract: Recently, on the basis of the effects of serotonin (5-HT) reuptake inhibitors in obsessive-compulsive disorder (OCD) treatment, several candidate genes related to 5-HT regulation have been hypothesized to play an important role in the development of OCD. One of them is 5-HT transporter gene. Therefore, the aims of this study were to investigate the associations between 5-HT transporter polymorphism and OCD. One hundred and twenty-four OCD patients and 171 normal controls participated in this study. Genomic DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 52 publications
(33 reference statements)
0
40
0
Order By: Relevance
“…Four studies involving 679 participants were conducted on children (26-29), and 17 studies involving 4,445 participants were of adults (6,10,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(30)(31)(32)(33). The factor structure of the studies involving adults was identical to those involving the total sample.…”
Section: Factor Analysis Results For Studies Involving Adults and Chimentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies involving 679 participants were conducted on children (26-29), and 17 studies involving 4,445 participants were of adults (6,10,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(30)(31)(32)(33). The factor structure of the studies involving adults was identical to those involving the total sample.…”
Section: Factor Analysis Results For Studies Involving Adults and Chimentioning
confidence: 99%
“…Eight studies involving 1,917 subjects involved subjects from non-English-speaking countries (15,17,19,22,24,26,30,33). Factor analysis generated a four-factor solution that explained 77.8% of the variance.…”
Section: Factor Analysis Results For Studies Involving English-speakimentioning
confidence: 99%
See 1 more Smart Citation
“…1 In terms of 5-HTTLPR, individuals with l/l (n ¼ 52) and l/s (n ¼ 219) genotypes were merged together as in previous research (Kim et al, 2005). For Stin2, there were few participants with 10R/ 10R (n ¼ 3), 12R/13R (n ¼ 2), 12R/14R (n ¼ 2) and 12R/15R (n ¼ 2).…”
Section: Discussionmentioning
confidence: 99%
“…The 10R allele of STin2 has been associated with lower transcriptional activity than the 12R allele (Fiskerstrand et al, 1999). Earlier studies Hu et al, 2006;Kim et al, 2005;McDougle et al, 1998) and a recent review (Bloch et al, 2008b) reported that the l allele of 5-HTTLPR was a risk factor for OCD while some other studies reported that the s allele was a risk factor (Lin, 2007;Perez et al, 2006). As mentioned early, interactions of SLCA64 by gender on OCD (Dickel et al, 2007;Voyiaziakis et al, 2011) and OCPD (Blom et al, 2011), were also reported.…”
mentioning
confidence: 89%